2002
DOI: 10.1039/b207523g
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hydroponic fertilizer matrixes for perchlorate: comparison of analytical techniques

Abstract: Seven retail hydroponic nitrate fertilizer products, two liquid and five solid, were comparatively analyzed for the perchlorate anion (ClO4-) by ion chromatography (IC) with suppressed conductivity detection, complexation electrospray ionization mass spectrometry (cESI-MS), normal Raman spectroscopy, and infrared spectroscopy using an attenuated total reflectance crystal (ATR-FTIR) coated with a thin film of an organometallic ion-exchange compound. Three of the five solid products were found by all techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…While significant natural sources of perchlorate are restricted to mineral deposits in Chile, environmental contamination with this compound results from its extensive use as an oxidizer in pyrotechnics and rocket fuel and its presence in certain fertilizers (9). Intake of perchlorate by humans occurs mainly via drinking water, milk, and certain consumed plants and should be minimized since this chemical affects hormone production by the thyroid gland (39).…”
mentioning
confidence: 99%
“…While significant natural sources of perchlorate are restricted to mineral deposits in Chile, environmental contamination with this compound results from its extensive use as an oxidizer in pyrotechnics and rocket fuel and its presence in certain fertilizers (9). Intake of perchlorate by humans occurs mainly via drinking water, milk, and certain consumed plants and should be minimized since this chemical affects hormone production by the thyroid gland (39).…”
mentioning
confidence: 99%
“…In many parts of the world, extensive perchlorate contamination of the surface and groundwater detected in 1997 with the development of instrumental techniques that uses highly sensitive chromatography which allowed the detection level less than 4 µg/L. These techniques demonstrated that the real extend of perchlorate contamination was underestimated [1,3]. In many parts of the world, extensive presence of perchlorate has been detected in measurable quantities in rice, fish and dairy products, vegetables and even breast milk [4,5].…”
Section: Introductionmentioning
confidence: 98%
“…Seven retail hydroponic nitrate fertilizer products, two liquid and five solid, were also tested for perchlorate. The test results indicated that three of the five solid products contained perchlorate ranging from about 100 to 350 mg/kg (Collette et al, 2003). Other investigators have reported perchlorate in fertilizers not derived from Chilean nitrate deposits (Susarla et al, 1999(Susarla et al, , 2000Urbansky et al, 2000).…”
Section: Perchlorate In Fertilizermentioning
confidence: 95%
“…Lithium carbonate and boric acid are extracted from these ponds and remaining salts are processed for potassium chloride, potassium sulfate, and fertilizers. Deposits mined for this fertilizer contains 6.3% nitrate, and from 0.1 to 0.03% perchlorate (Collette et al, 2003;Grossling and Erickson, 1971;Tian et al, 2005;Urbansky, Brown, et al, 2001;Urbansky, Collectte, et al, 2001). Presence of perchlorate in groundwater originating from perchlorate enriched deposits in the Atacama Desert is well known (Crump et al, 2000).…”
Section: Perchlorate In Fertilizermentioning
confidence: 95%